2020
DOI: 10.1155/2020/2398693
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Fly Ash‐Based Geopolymers as a Modifier for Asphalt Binders

Abstract: Severe Canadian winter conditions and growing traffic volumes are vital factors resulting in a reduction of the service life of flexible pavements. Researchers and engineers strived to develop several additives to develop balanced asphalt mixers capable of resisting distresses that caused deterioration of flexible pavements in Canada. In this study, a critical literature review regarding the use of geopolymers and their application in construction materials is provided. Moreover, an experimental matrix of labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 30 publications
(35 reference statements)
2
22
0
Order By: Relevance
“…However, many fly ash-based geopolymers previously reported in the literature for different purposes and applications could be improved by applying the formulations developed in this study. These formulations could be used to improve the fly ash-based geopolymer coating for fire resistance materials [ 32 ], the immobilization of hazardous substances [ 25 ] and backfilling materials [ 71 ], low micro-filling effect (low porosity) materials [ 24 ], absorbent materials [ 44 ], or asphalt binders [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many fly ash-based geopolymers previously reported in the literature for different purposes and applications could be improved by applying the formulations developed in this study. These formulations could be used to improve the fly ash-based geopolymer coating for fire resistance materials [ 32 ], the immobilization of hazardous substances [ 25 ] and backfilling materials [ 71 ], low micro-filling effect (low porosity) materials [ 24 ], absorbent materials [ 44 ], or asphalt binders [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several authors have investigated the synthesis of geopolymers with fly ash for different purposes and applications. For instance, Hamid et al [ 43 ] reported that a geopolymer could potentially enhance some of the properties of the asphalt binder. Wang and Zhao [ 32 ] demonstrated that a dosage of 25 wt% of fly ash or slag was crucial to obtain excellent flame retarding efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Industries and companies' sealants [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Heat resistance and fire resistances fiber composites…”
Section: Geopolymer Applicationmentioning
confidence: 99%
“…Furthermore, at low and high stress levels, modified asphalt binder containing 8% geo fly ash had better rutting resistance than 4 and 12% geopolymer. Also, a study was carried out by Alfaidi et al [32] to evaluate the effects of geopolymer curing on rheological bitumen properties. The outcomes show that the time of curing affects the bitumen rheological performance by increasing its complex shear modulus, temperature, and viscosity.…”
Section: Figurementioning
confidence: 99%
“…It is known [ 33 , 34 ] that the main problem associated with road construction in the Arctic zone is swelling of the soil due to the freezing of the moisture contained in it. This is due to waterlogging of the soil and long periods with a negative ambient temperature.…”
Section: Introductionmentioning
confidence: 99%